2010
DOI: 10.1590/s0001-37652010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Histological modifications of the rat prostate following transection of somatic and autonomic nerves

Abstract: It is known that hormones influence significantly the prostate tissue. However, we reported that mating induces an increase in androgen receptors, revealing a neural influence on the gland. These data suggested that somatic afferents (scrotal and genitofemoral nerves) and autonomic efferents (pelvic and hypogastric nerves) could regulate the structure of the prostate. Here we assessed the role of these nerves in maintaining the histology of the gland. Hence, afferent or efferent nerves of male rats were transe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Similar findings have been reported in other neurotrophic cancer such as pancreatic cancer(13). Studies in rats have shown that denervation of the prostate leads to almost complete loss of epithelium (14), indicating a strong trophic effect of nerves on normal prostate epithelium. Similarly, men with complete spinal cord injury had significantly smaller prostates than controls(15).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in other neurotrophic cancer such as pancreatic cancer(13). Studies in rats have shown that denervation of the prostate leads to almost complete loss of epithelium (14), indicating a strong trophic effect of nerves on normal prostate epithelium. Similarly, men with complete spinal cord injury had significantly smaller prostates than controls(15).…”
Section: Introductionmentioning
confidence: 99%
“…The optimized direct administration protocol was applied to the rat hypogastric nerve and aortic plexus, which served as surgically accessible autonomic nerves that model the composition and smaller size of the cavernous nerves as compared to the brachial plexus and sciatic nerves used for murine studies 51 , 58 , 59 . The rat doses of Oxazine 4 and Nile Red for both direct and systemic administration were scaled from the murine studies by body surface area equivalence 65 .…”
Section: Resultsmentioning
confidence: 99%
“…The optimized direct administration method using Oxazine 4 alone and in combination with Nile Red was scaled to rat imaging studies to facilitate imaging of surgically available autonomic nerves that were in close anatomical proximity to the prostate with similar composition to the cavernous nerves 51 , 58 , 66 . The aortic plexus and hypogastric nerves were selected for direct administration studies where the hypogastric nerves were larger and more easily visualized than the aortic plexuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, while GDNF signalling is important for kidney development and spermatogenesis (Sariola & Saarma 2003), the role of other GDNF families of neurotrophic factors outside the nervous system is not well understood. In humans and rodents, the prostate gland has a rich sympathetic and parasympathetic innervation (Vaalasti & Hervonen 1979, 1980, and previous rodent studies of autonomic denervation have suggested significant (Martinez-Pineiro et al 1993, Lujan et al 1998, Diaz et al 2010) but complex and ill-defined roles of autonomic nerves in the regulation of glandular structure and function. Therefore, the original aim of this study was to utilise transgenic mouse models lacking either a ligand (NTNKO) or a receptor (GFRa2KO) for the NTN signalling pathway to characterise the role and signalling mechanisms of parasympathetic nerves in prostate development.…”
Section: Discussionmentioning
confidence: 99%